Rainbow Trapping in Highly Doped Silicon Graded Grating Strip at the Terahertz Range - Yan Liu; Ruoying Kanyang; Genquan Han; Yao Shao; Cizhe Fang; Yan Huang; Siqing Zhang; Jincheng Zhang; Yue Hao (IEEE Photonics Journal, 2018)
In this paper, we propose surface plasma polaritons (SPPs) propagating along the structure of grating grooves based on highly doped silicon, which exhibits better performance of exciting SPPs than metal at low frequency (e.g., microwaves, mid infrared, and terahertz). The dispersive properties of the gradient-corrugated grating waveguides are characterized using the computer simulation technology microwave studio. Moreover, the propagation characteristics of the highly doped silicon grating structure are analyzed in detail by the dispersion curves, two-dimensional electric field magnitude distributions, the propagation loss, and the SPP lifetime. It is demonstrated that the gradient-corrugated grating waveguides based on heavily doped silicon could excite SPPs and realize rainbow trapping. The lifetime of the plasmonic mode can reach a value of 1200 ps, which may be long enough for some meaningful nanophotonic applications. The highly doped silicon is an ideal candidate for making practical use of the slow-light system in optical communication and various nanophotonic circuits, which permits further application for compact plasmonic devices.